2007
DOI: 10.1158/0008-5472.can-07-0778
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic NRAS, KRAS, and HRAS Exhibit Different Leukemogenic Potentials in Mice

Abstract: RAS proteins are small GTPases that play a central role in transducing signals that regulate cell proliferation, survival, and differentiation. The RAS proteins interact with a common set of activators and effectors; however, they associate with different microdomains of the plasma membrane as well as other endomembranes and are capable of generating distinct signal outputs. Mutations that result in constitutive activation of RAS proteins are associated with f30% of all human cancers; however, different RAS on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 27 publications
(27 reference statements)
5
69
0
1
Order By: Relevance
“…The transduction was performed as described previously. 24,51,52 The expression of let-7a and KRas were detected by qRT-PCR and Western blot analysis as described below.…”
Section: Constructs and Transfectionmentioning
confidence: 99%
“…The transduction was performed as described previously. 24,51,52 The expression of let-7a and KRas were detected by qRT-PCR and Western blot analysis as described below.…”
Section: Constructs and Transfectionmentioning
confidence: 99%
“…of Helios-deregulated T-ALL (20). In addition, we observed that ectopic expression of Helios-Δ326-1431 led to the upregulated expression of HRAS, which exhibited leukemogenic potential in myeloid-lineage leukemia (21). Furthermore, this study identified that other components of the RAS signaling pathway, such as RASSF7, RAB40B, and RASIP1, were upregulated in the Helios-Δ326-1431 overexpressed cells.…”
Section: Discussionmentioning
confidence: 60%
“…Retroviral constructs expressing NRAS-G12D, KRAS4A-G12D, KRAS4B-G12D, and NRAS-G12D-C181S as N-terminal GFP-fusion proteins were generated as previously described (19,22). The retroviruses were produced using Bosc23 cells and were titered as previously described (22).…”
Section: Dna Construction and Retrovirus Productionmentioning
confidence: 99%
“…The growth factor dependent Ba/F3 cells were cultured in RPMI 1640 (Gibco), including 10% fetal bovine serum (FBS, Gibco), and supplemented with 15% WEHI-3-conditioned medium as a source of IL3 or with recombinant IL3 (Roche) at the final concentration of 1 ng/mL. The Ba/F3 and NIH3T3 cells were transduced with retroviruses as described (22,24). The HeLa cell line was bought from ATCC in 2009 and cultured according to the instruction.…”
Section: Cell Culture and Retroviral Transductionmentioning
confidence: 99%
See 1 more Smart Citation